Classification, diagnosis, and approach to treatment for angioedema: consensus report from the Hereditary Angioedema International Working Group. Issue 5 (27th March 2014) - Cicardi, M.; Aberer, W.; Banerji, A.; Bas, M.; Bernstein, J. A.; Bork, K.; Caballero, T.; Farkas, H.; Grumach, A.; Kaplan, A. P.; Riedl, M. A.; Triggiani, M.; et al.
Abstract Angioedema is defined as localized and self‐limiting edema of the subcutaneous and submucosal tissue, due to a temporary increase in vascular permeability caused by the release of vasoactive mediator(s). When angioedema recurs without significant wheals, the patient should be diagnosed to have angioedema as a distinct disease. In the absence of accepted classification, different types of angioedema are not uniquely identified. For this reason, the European Academy of Allergy and Clinical Immunology gave its patronage to a consensus conference aimed at classifying angioedema. Four types of acquired and three types of hereditary angioedema were identified as separate forms from the analysis of the literature and were presented in detail at the meeting. Here, we summarize the analysis of the data and the resulting classification of angioedema.